2018
DOI: 10.1016/j.rssm.2018.03.001
|View full text |Cite
|
Sign up to set email alerts
|

What explains the negative effect of unemployment on health? An analysis accounting for reverse causality

Abstract: The unemployed are often in poorer health than their employed counterparts. This cross-sectional correlation is often attributed to a causal effect of unemployment on health. Resent research analyzing longitudinal data, however, often supports alternative explanations, such as spurious correlation and/or selection of unhealthy workers into unemployment (i.e., reverse causality). In this paper, we apply a dynamic panel data estimator (system GMM) to account for both unobserved confounders and reverse causality.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
49
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
3
1

Relationship

3
5

Authors

Journals

citations
Cited by 64 publications
(51 citation statements)
references
References 79 publications
1
49
0
1
Order By: Relevance
“…In contrast, both the number of strong ties and the amount of conflict in the household had statistically significant impacts on mental health, but there was no corresponding effect of unemployment on these two measures. In all, our results are in line with the previous, albeit limited, empirical evidence regarding the potential of unemployment to exert detrimental mental health effects via its adverse effects on social integration, including the only fixed effects regression (that we are aware of) that addresses the causal path hypothesis (Krug, Eberl 2018).…”
Section: Discussion and Limitationssupporting
confidence: 91%
See 2 more Smart Citations
“…In contrast, both the number of strong ties and the amount of conflict in the household had statistically significant impacts on mental health, but there was no corresponding effect of unemployment on these two measures. In all, our results are in line with the previous, albeit limited, empirical evidence regarding the potential of unemployment to exert detrimental mental health effects via its adverse effects on social integration, including the only fixed effects regression (that we are aware of) that addresses the causal path hypothesis (Krug, Eberl 2018).…”
Section: Discussion and Limitationssupporting
confidence: 91%
“…Janlert and Hammarström (2009) used data from 1,044 school leavers and found that the amount of social support at age 30, measured by the availability of social interaction and the availability of attachment, mediates the negative effect on physical health of the total amount of time in unemployment between the ages of 16 and 30 but not the negative effect of the same variable on mental health. Janlert and Hammarström (2009) used longitudinal information, but to the best of our knowledge, the only study that used panel data and explicitly controlled for unobserved confounders was from Krug and Eberl (2018). Based on a general population survey and panel data regressions, the authors found that neither the number of strong ties (close friends and relatives outside the household) nor the availability of weak ties through memberships in voluntary leisure organizations mediates the causal effect of unemployment on selfrated health and mental health.…”
Section: State Of Empirical Researchmentioning
confidence: 99%
See 1 more Smart Citation
“…In the UK, the consensus on pursuing a "welfare to work" agenda for people with disabilities generally (Department for Work and Pensions & Department of Health, 2017) has been underpinned in part by the rhetoric of better health and mortality outcomes associated with employment (Black, 2008). Whilst the causal pathways between employment and health have been reasonably well-established in the general population (Bartley, 1994;Janlert & Hammarström, 2009;Krug & Eberl, 2018), at present, there is insufficient evidence to determine causality in relation to the association between employment and health for people with intellectual disabilities. Further research to determine specific health benefits attributable to employment for people with intellectual disabilities is required, as well as research to elucidate the causal pathways that operate with reference to existing models on the relationship between (un)employment and health in the general population (e.g., Janlert & Hammarström, 2009, Paul & Moser, 2006.…”
Section: Con Clus Ionmentioning
confidence: 99%
“…Additionally, threats to social identity status in severe discriminations, intense power, and status struggle (e.g., caste system, slavery), and unemployment are not directly included in any of current popular frameworks. The loss of self-perceived social status but not the loss of income or social support explained a significant variance for the adverse health effects of unemployment (Krug, & Eberl, 2018). While anxieties about existence can vary in their intensities, existential annihilation anxieties (EAA) represent the severe endpoints in the continuum of such anxieties.…”
Section: Introductionmentioning
confidence: 99%